Advancements and future prospects in the fundamental theories of rock blasting research Ⅲ—Interaction mechanism between blast waves and cracks - Peng XU; Renshu YANG; Cheng CHEN; Chenxi DING; Yanbing WANG (工程科学学报)
The “three relationships (the relationship between rock failure characteristics and blast loading, the superposition effect between blast waves and explosion gas, and the interaction between blast waves and cracks)” are important contents of the rock blasting theory. Of these, the interaction between blast waves and cracks is the key factor affecting rock fragmentation. Aiming at the key scientific issue of “fine control principle of explosive energy release and blast induced crack propagation”, this paper focuses on the crack–wave interaction problem, which can be divided into four aspects, including the interaction between blast waves and stationary cracks (the existed defects in rock mass), the interaction between blast waves and blast-induced cracks, the interaction among cracks under the action of blast waves, and the propagation behavior of cracks under the superposition of geostress and blast waves. Focusing on these four aspects, we systematically analyzed the influence of blast waves propagation direction and its intensity on crack propagation behaviors, including the crack propagation direction, crack velocity and crack length. In order to observe the interaction process between blast waves and cracks, we develop a series of new optical experimental systems with blast loading, including the dynamic caustics experimental system and photoelasticity system. First, for blast waves encountering a stationary crack, we conduct a caustics experiment, following which both the variation in caustic patterns and the stress field around the crack tip are obtained during the crack–wave interaction; it is observed that the wing crack is more easily generated at the horizontal pre-crack than at the vertical pre-crack. Moreover, using the photoelastic technique, we clearly observe both the reflection and diffraction processes of blast waves when they encounter the stationary crack; in addition, a “double Mach cone” phenomenon occurs around the stationary crack, following which a high amount of explosive energy accumulates around the crack, resulting in severe damage around the crack. Second, for the interaction between blast waves and dynamic cracks, using the photoelastic experiment, we observe that the dilatational wave suppresses the propagation of the oppositely propagating crack, whereas the shear wave facilitates the propagation of the oppositely propagating crack. However, during the interaction between blast waves and a blast-induced crack in the same direction, the dilatational wave facilitates the propagation of the crack, but the shear wave suppresses its propagation. Furthermore, we observe that the propagation direction of the crack can be apparently changed when it obliquely encounters the blast waves; the crack propagates in the clockwise direction when the stress intensity factor KII of the crack tip is positive but propagates in the counterclockwise direction when KII becomes negative. Third, for crack interaction during double borehole blasting, two oppositely propagating cracks are made to interact with each other, resulting in a “linking effect” and forming an interconnected shape. Last, we observe that geostress can facilitate the propagation of blast-induced cracks parallel to the direction of maximum principal stress and suppress the propagation of blast-induced cracks perpendicular to the direction. Moreover, the higher the difference between principal stresses in the geostress field, the greater the propagation length of blast-induced cracks along the direction of maximum principal stress. The research results provide theoretical guidance for optimizing parameters, such as blasting hole spacing and delay time, and achieving fine control of blast induced crack propagation.